Local responses to a national initiative on organised crime and local government procurement fraud. Issue 1 (22nd January 2020) - Doig, Alan; Sproat, Peter A.
Abstract : Purpose: The purpose of this paper is to research how local councils in England responded to a national initiative intended to address the risk of the involvement of organised crime in local government procurement fraud. In so doing, it considers definitional issues before undertaking original research to explore how councils responded and, through in-depth interviews with three councils, what initial explanations may explain the responses. It concludes that the national initiative was insufficiently thought-through, and that councils' responses were significantly influenced by the relevance of the threat of organised crime, financial constraints and competing priorities. Design/methodology/approach: The case study involves a literature review, an analysis of official documentation, a questionnaire to local councils in the north of England and semi-structured interviews with anti-fraud practitioners in three councils in the northeast of England. The approach is to provide an analysis of the implementation of a national initiative to promote a local government response to procurement fraud by organised crime. Findings: On the basis of original research, the paper proposes that the national initiative was insufficiently thought-through, and that councils' responses were influenced by the relevance of the threat of organised crime, financial constraints and competing priorities. Research limitations/implications: The research looks at a national initiative and how local councils responded within the context of financial and other constraints. The research is limited in terms of the range of responses it sought, and that it only studied the experience of three local councils in detail. On the other hand, its findings support further research into the implementation of national initiatives in terms of practice on the ground. Practical implications: The findings identify issues surrounding the design and implementation of national anti-fraud policies from the perspective of local government and will be of value to practitioners and academics interested in fraud, policing, organised crime, local government and policy making. Originality/value: The paper is the first study in the UK on the local implementation of national strategies on procurement fraud and organised crime and raises positive and less-positive aspects of how far national strategies and intentions are addressed on the ground, with a focus on what factors may influence local implementation.